31 Dynamic change of PD-L1 expression on extracellular vesicles predicts response to immune-checkpoint inhibitors in non-small cell lung cancer patients. (9th November 2020) - Perez, Diego de Miguel; Russo, Alessandro; Gunasekaran, Muthukumar; Cardona, Andrés; Lapidus, Rena; Cooper, Brandon; Kaushal, Sunjay; Peterson, Christine; Colen, Rivka; Naing, Aung; Adamo, Vincenzo; Rolfo, Christian
Abstract : Background: Immune-checkpoint inhibitors (ICIs) have revolutionized the treatment of advanced/metastatic non-small cell lung cancer patients (NSCLC), however, only a small subset of patients derives clinical benefit. 1–3 To date, PD-L1 immunohistochemical evaluation is the gold-standard assay and the only approved biomarker, but associated with several limitations due to technical and biological factors such as spatial and temporal tumor heterogeneity. 4 5 In this context, liquid biopsies emerge as novel powerful tools that could allow the non-invasive real-time characterization of the tumor PD-L1 status. In particular, extracellular vesicles (EVs), defined as cell-derived double-membrane structures involved in cell communication, hold strong potential as tissue surrogates. Recent studies have suggested that EV PD-L1 could stratify melanoma patients receiving ICIs, but none has showed the predictive value of this biomarker in NSCLC patients. 6 7 We hypothesize that EV PD-L1 cargo can serve to stratify the response to ICIs in NSCLC patients. Methods: This study enrolled advanced/metastatic NSCLC patients receiving ICI treatment. Plasma samples were obtained at baseline (T1) and at 8 weeks (T2) during the first response evaluation. Patients were classified as responders when showing partial, stable or complete response or as non-responders when manifesting progressive disease following RECIST v1.1. 8 Plasma EVs were isolated by standard serial ultracentrifugation methods and characterized according to ISEV recommendations. 9 10 Tissue PD-L1 expression was measured by immunohistochemistry while EV PD-L1 expression was measured by immunoblot. A predictive model was created by logistic-regression and a bootstrap corrected ROC curve to validate the results. Results: Paired plasma samples from 21 patients were analyzed. PD-L1 tissue expression was not correlated with treatment response (p=0.394) nor matched the baseline EV PD-L1 levels (p=0.337) (figure 1.A). However, the dynamics of EV PD-L1 (T1-T2) correlated with the treatment response, observing an increase of PD-L1 expression in non-responders and a decrease or stable levels in responders (p=0.043) (figure 1.B). The predictive model reported an AUC=0.85, 90% CI=0.72–0.97, with 74.2% sensitivity and 73.5% specificity (figure 1.C). Moreover, the increase of EV PD-L1 was associated with shorter overall survival (HR=4.34, p=0.037) and shorter progression-free survival (HR=5.06, p=0.025) (figure 1 D & E). Conclusions: Our preliminary-study showed, for the first time, the predictive and prognostic value of EV PD-L1 dynamic changes in immunotherapy-treated NSCLC patients. Although larger studies are needed to validate these results, this promising biomarker could have important clinical implications, guiding treatment decisions in near real-time and improving the outcome of patients that could benefit from ICIs. Acknowledgements: We would like to extend our gratitude to the all the patients that participated in the study. Ethics Approval: All patients consented to an Institutional Review Board–approved protocol (A.O. Papardo, Messina, Italy). Biological material was transfer to the University of Maryland, USA under signed MTA between both institutions (MTA/2020-13111). References: Rittmeyer A, Barlesi F, Waterkamp D, et al. Atezolizumab versus docetaxel in patients with previously treated non-small-cell lung cancer (OAK): a phase 3, open-label, multicentre randomised controlled trial. Lancet 2017;389:255–265. Borghaei H, Paz-Ares L, Horn L, et al. Nivolumab versus Docetaxel in Advanced Nonsquamous Non-Small-Cell Lung Cancer. N Engl J Med 2015;373:1627–1639. Chen DS, Mellman I: Oncology Meets Immunology: The Cancer-Immunity Cycle. Immunity 2013, 39:1–10. Zou WP, Wolchok JD, Chen LP. PD-L1 (B7-H1) and PD-1 pathway blockade for cancer therapy: Mechanisms, response biomarkers, and combinations. Sci Transl Med . 2016; 8:328rv4. Patel SP, Kurzrock R. PD-L1 Expression as a predictive biomarker in cancer immunotherapy. Mol Cancer Ther 2015;14:847–56. Cordonnier M, Nardin C, Chanteloup G, et al. Tracking the evolution of circulating exosomal-PD-L1 to monitor melanoma patients. J Extracell Vesicles 2020;9:1710899. Del Re M, Marconcini R, Pasquini G, et al. PD-L1 mRNA expression in plasma-derived exosomes is associated with response to anti-PD-1 antibodies in melanoma and NSCLC. Br J Cancer 2018;118:820–824. Eisenhauer EA, Therasse P, Bogaerts J, et al . New response evaluation criteria in solid tumours: revised RECIST guideline (version 1.1). Eur J Cancer 2009;45:228–47. Reclusa P, Verstraelen P, Taverna S, et al. Improving extracellular vesicles visualization: From static to motion. Sci Rep 2020;10(1):6494. Thery C, Witwer KW, Aikawa E, et al . Minimal information for studies of extracellular vesicles 2018 (MISEV2018): a position statement of the International Society for extracellular vesicles and update of the MISEV2014 guidelines. J Extracell Vesicles 2018;7:1535750.